A sensitive sandwich structure time-resolved fluorescence method for thrombin detection. Issue 34 (17th August 2018) - Wu, Tao; Zhang, Yuanfu; Hou, Tingting; Zhang, Yinghong; Wang, Shuhao
Abstract : We designed a sensitive and specific time-resolved fluorescence assay for detection of human thrombin. Abstract : We designed a sensitive and specific time-resolved fluorescence assay for detection of human thrombin. This design was based on the amplification of nanoparticles and the specificity of aptamers. The DC@AuNPs were prepared by the conjugation of AuNPs to BSA–Eu 3+ –DTPA and SH-Apt29. In the presence of thrombin, the formation of a quadruplex–thrombin complex could lead to the formation of a MNPs@Apt15–thrombin–DC@AuNP sandwich structure. In the presence of enhancement solution, Eu 3+ interacted with the enhancement solution to produce strong fluorescence. Under the optimized conditions, the linear range of the method was from 1 pM to 100 pM of thrombin, and the limit of detection was 0.78 pM. Furthermore, the method could specifically recognize thrombin in the presence of other analogous proteins. The method is successfully used to determine thrombin in human plasma. This method has the advantages of high sensitivity and selectivity. It showed great potential for medical diagnosis.